Modelling Attitude towards Consumption of Vegan Products - Miguel, Isabel (2020)
This study proposes to understand the impact of personal (health awareness and social influence) and moral (environmental concerns and animal welfare) antecedents on attitudes towards veganism and their effects on engagement with vegan products, along with their impact on purchase intention and word of mouth. Idealism is presented as a moderator of these proposed relationships. The study uses a structured questionnaire to gather data from two cross-sectional samples of 224 Portuguese and 356 Brazilian vegans collected from Facebook groups of vegans. Structural equation modelling is used to test the seven proposed hypotheses and the moderation effects. This research compares the influence of personal and moral determinants on veganism using idealism as a specific context to investigate their relationships, comparing Brazilian and Portuguese respondents and the effects of national cultures. Results show that attitudes towards veganism do not depend on personal causes, but rather on moral concerns. Motivations to reduce animal consumption, protect nature, and respect animal life seem to be guided by ethical principles.